Long-Term Angiographic Results of Recanalization of Small Diameter Coronary Arteries in Patients with Coronary Heart Disease - Aksenov, E. V.; Demchenko, R. B. (Ukrainian Journal of Cardiovascular Surgery, 2021)
One of the most serious problems of modern times are cardiovascular diseases, and these are the leading cause of death worldwide. The main contribution to the structure thereof belongs to coronary heart disease (CHD) which has become the greatest threat to the health of the population all over the world. The aim. To study the results of endovascular procedures in revascularization of small diameter coronary arteries. Materials and methods. The study included 417 patients aged 59 to 78 years with a mean diameter of the true in-ternal lumen of the arteries of 2.75±0.016 mm who underwent revascularization of the myocardium through stenting or percutaneous transluminal balloon coronary angioplasty (PTCA). In patients undergoing stenting of coronary artery (N=269), the mean diameter of the true internal lumen of the arteries was 2.68±0.03 mm. In the group of patients who underwent PTCA (N=148), this indicator was found to be 2.61±0.09 mm. The average degree of stenosis was 81.3±4.07%. The length of the artery stenosis was 12.4±0.71 mm. All the patients had the history of Q wave myocardial infarction (MI) more than 3 months ago, which made it possible to diagnose postinfarction cardiosclerosis. Ischemic history of more than 5 years was noted in 46 patients of this group (11.03% of cases), up to one year in 221 patients (70.2% of cases), from 1 to 2 years in 41 patients (9.83% cases), and 3 to 4 years in 38 people (9.11% of cases). Results and discussion. As a result of the studies, it was found that in patients with eccentric type of stenosis who used balloon angioplasty, restenosis in the remote postoperative period was 21% more frequent compared to a similar contingent of patients with implanted stents. In addition, restenosis of the stenosed area of the coronary artery > 1.5 mm in the distant period was 14.9% more common when PTCA was performed. And the frequency of remote restenosis (with complex morphology of initial damage of the arteries) in the stenting group was 14.2% lower than in the group of PTCA. Additionally, in the group of patients who underwent stenting, neoatherosclerosis in the treated segment was found in 92 patients (34.2 %). Patients with PTCA had a less progress of atherosclerosis (44 patients 29.72%) Conclusions. Restenosis in the remote postoperative period was 25.4 % less frequent in patients with eccentric ste-nosis who underwent stenting than in patients with balloon angioplasty. At the same time, restenosis of the stenosed area of CA >15 mm in the distant period was 10.43% more frequent during PTCA. In the coronary angioplasty group, patients with complicated morphology of basal damage of arteries had a 21.67% higher incidence of restenosis than in the coro-nary stenting group. Thus, we plan to carry out further study and analysis of immediate and long-term results of X-ray and endovascular operations in patients with coronary artery disease and small coronary artery diameter.